In-situ generated high-entropy particle reinforced magnesium-based composite material and preparation method thereof

By generating high-entropy particle reinforcement materials in situ within a magnesium matrix, the problems of insufficient interfacial bonding and limited strength improvement in magnesium-based composite materials are solved, achieving synergistic optimization of strength, hardness, and ductility, making it suitable for lightweight industries such as aerospace and automotive.

CN121700262APending Publication Date: 2026-03-20CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511906792.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-17
Publication Date
2026-03-20

AI Technical Summary

Technical Problem

Existing magnesium-based composite materials have limited ductility and absolute strength at room temperature. Traditional external reinforcing particles suffer from insufficient interfacial bonding and limited strength improvement from alloying, making it difficult to achieve synergistic optimization of strength, hardness, and ductility.

Method used

In-situ generation of high-entropy particles to reinforce magnesium matrix composites is employed. By adding Y, Dy, Ho, and Er elements to the magnesium matrix, Mg24(Y0.25Dy0.25Ho0.25Er0.25)5 high-entropy particles are formed. Utilizing their high strength, high hardness, and lattice distortion effect, coherent interfacial bonding with the magnesium matrix is ​​achieved, thereby improving the overall mechanical properties of the material.

Benefits of technology

It significantly improves the room temperature strength and ductility of composite materials. The resulting high-entropy particle reinforcement has high strength and high hardness, and good interfacial bonding. It is suitable for large-scale production, has low cost, and is applicable to the lightweight industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121700262A_ABST
    Figure CN121700262A_ABST
Patent Text Reader

Abstract

The invention discloses an in-situ generated high-entropy particle reinforced magnesium-based composite material and a preparation method thereof, the composite material comprises Mg, Y, Dy, Ho and Er elements, the atomic ratio of Mg / Y + Dy + Ho + Er is greater than 10: 1, and the atomic ratio of Y to Dy to Ho to Er is 1: 1: 1: 1. The atomic ratio of Mg / Y + Dy + Ho + Er is larger than 10: 1, the atomic ratio of Y, Dy, Ho and Er is 1: 1: 1: 1: 1, Mg24 (Y0.25 Dy0.25 Ho0.25 Er0.25) 5 high-entropy particles can be generated after rare earth atoms are subjected to solid solution, the high-entropy particles serving as reinforcements have high strength and high hardness, and the strength and hardness of the composite material can be remarkably improved; meanwhile, in-situ synthesized Mg24 (Y0. 25Dy0. 25Ho0. 25Er0. 25) 5 high-entropy particles and an Mg matrix form a coherent interface, dislocation can be extended, plastic deformation of the material is coordinated, and when the room temperature of the prepared composite material is 25 DEG C, the yield strength is 212 MPa, the tensile strength is 361 MPa, the Vickers hardness is 107 Hv, and the ductility is 10.6%; the high-entropy particle reinforced Mg-based composite material is generated in situ, so that the room-temperature strength and ductility of the alloy can be synergistically improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of magnesium-based composite materials technology, specifically relating to an in-situ generated high-entropy particle-reinforced magnesium-based composite material and its preparation method. Background Technology

[0002] Magnesium (Mg) alloys are considered promising lightweight structural materials due to their low density and high specific strength, especially in transportation and aerospace. However, their limited ductility and absolute strength at room temperature have consistently restricted their widespread application. To overcome this limitation, researchers have explored various methods, which can be mainly categorized into two types: the first type involves introducing a second phase, such as ceramic particles, heterometallic materials (e.g., titanium, iron), or even carbon nanotubes (CNTs); the second type involves alloying treatment, i.e., solid-solution treatment with other alloying elements, such as Al, Zn, or rare earth elements like Y and Gd.

[0003] Initially, to meet the demands of industrial production, low-cost ceramic particles were used. Specifically, hard ceramic particles such as silicon carbide (SiC) or aluminum nitride (AlN) were incorporated into a magnesium matrix to prepare SiC / Mg and AlN / Mg composites, which significantly improved mechanical properties—strength exceeding 300 MPa and Vickers hardness exceeding 70 Hv. As industrial demands increased, fiber-reinforced materials with ultra-high strength gradually replaced ceramic particles. For example, CNTs / Mg composites formed by adding carbon nanotubes (CNTs) showed significantly improved strength (>300 MPa) even at low addition levels. However, the poor wettability between the inert CNT surface and the Mg matrix resulted in persistently low ductility. To address this issue, metal reinforcing phases were introduced to utilize their excellent intermetallic wettability. For example, incorporating Ti particles into Mg to form Ti / Mg composites promoted strong metallurgical bonding and improved ductility (by more than 5%). However, the agglomeration of Ti particles in the Mg matrix and the interfacial mechanical bonding with the Mg matrix still limited further improvements in ductility.

[0004] To further address the challenges of dispersion and interfacial bonding, alloying methods were employed. The solid solubility of certain elements in magnesium exceeding 10 at.% can produce a solid solution strengthening effect. For example, the addition of trace amounts of yttrium (Y) or strontium (Sr) can increase tensile strength beyond 230 MPa, while 10% yttrium or gadolinium (Gd) content can raise the strength to over 280 MPa while maintaining 10% ductility. When multiple elements (such as Mg-Gd-Y-Zn, Mg-Al-RE) are added to the Mg matrix, the tensile strength can reach 330 MPa, with ductility reaching 9%. This indicates that multi-element addition can achieve a better balance between strength and ductility, but the strength improvement is still not as significant as that of ceramic particles or fiber-reinforced materials.

[0005] In recent years, high-entropy alloys (HEAs) have attracted widespread attention in various fields due to their unique microstructure and superior mechanical properties (derived from the ultra-high strength and hardness of multi-principal element design). For example, Cantor alloy (CoCrFeMnNi) exhibits a strength exceeding 795 MPa and a ductility of 10%, while the eutectic HEA AlCoFeNi possesses a strength exceeding 956 MPa and a ductility of 10%. Numerous studies have shown that HEAs have four core effects that significantly enhance the strength of materials, making them a novel strengthening strategy for magnesium-based composites. Summary of the Invention

[0006] This invention aims to at least partially solve one of the technical problems in related technologies. Therefore, the main objective of this invention is to provide an in-situ generated high-entropy particle-reinforced magnesium matrix composite material with good strength, hardness, and ductility; The present invention also provides a method for preparing the in-situ generated high-entropy particle-reinforced magnesium matrix composite material, which aims to solve the problems of insufficient interfacial bonding of traditional external reinforcing particles and the limited strength improvement of traditional alloying, and to achieve synergistic optimization of the strength, hardness and ductility of the composite material.

[0007] The objective of this invention is achieved through the following technical solution: An in-situ generated high-entropy particle-reinforced magnesium-based composite material, the composite material comprising Mg, Y, Dy, Ho and Er elements, wherein the atomic ratio of Mg / Y+Dy+Ho+Er is > 10:1, and the atomic ratio of Y, Dy, Ho and Er is 1:1:1:1.

[0008] The composite material provided by this invention has a solid solubility of more than 10 wt.% of the four rare earth elements Y, Dy, Ho, and Er in Mg. After dissolving into the Mg crystals, each rare earth element precipitates out as a precipitate phase. This invention limits the atomic ratio of Mg / Y+Dy+Ho+Er to >10:1, and the atomic ratio of Y, Dy, Ho, and Er to 1:1:1:1, thus forming a Mg / Mg composite material after the rare earth atoms are dissolved. 24 (Y 0.25 Dy 0.25 Ho 0.25 Er 0.25 )5 composite material, forming Mg 24 (Y 0.25 Dy 0.25 Ho 0.25 Er 0.25)5 As a high-entropy particle reinforcement, it has high strength and high hardness, which can significantly improve the strength and hardness of composite materials. At the same time, high-entropy particles have lattice distortion effect and hysteresis diffusion effect, which can generate lattice distortion, resulting in the formation of coherent interfaces with Mg, extending dislocations, realizing the synergistic effect of reinforcement, and taking into account room temperature strength and ductility.

[0009] As part of the same inventive concept, this invention also provides a method for preparing the in-situ generated high-entropy particle-reinforced magnesium-based composite material, comprising the following steps: 1) According to the formula requirements, the composite material raw materials are mixed and melted, then poured into a mold, and after cooling, an alloy ingot is obtained; 2) The alloy ingot obtained in step 1) is homogenized and extruded to obtain an in-situ high-entropy particle-reinforced magnesium matrix composite material.

[0010] In some specific embodiments, the mixing and melting described in step 1) is specifically carried out under protective gas conditions.

[0011] In some specific embodiments, the mixing and melting step in step 1) includes the following steps: Under protective gas conditions, the prescribed amounts of Mg, Y, Dy, Ho and Er elements are heated and melted. After the base alloy is completely melted at 720-740℃, it is stirred evenly to obtain a magnesium alloy base melt.

[0012] In some specific embodiments, the protective gas is a mixture of CO2 and SF6 in a volume ratio of 99:1.

[0013] In some specific embodiments, the cooling in step 1) is water cooling, which specifically involves placing the ingot in cold water and slowly cooling it around the crucible for 30-60 seconds.

[0014] In some specific embodiments, the homogenization heat treatment in step 2) is performed at a temperature of 480-520°C for 12-18 hours.

[0015] In some specific embodiments, the extrusion molding conditions in step 2) are: extrusion temperature 420-480℃, extrusion ratio (15-20):1, and extrusion rate 0.5-2mm / s.

[0016] Compared with the prior art, the present invention has at least the following advantages: 1) The composite material provided by this invention has a solid solubility of more than 10 at.% for the four rare earth elements Y, Dy, Ho, and Er in Mg. After the rare earth elements are dissolved into the Mg crystals, they precipitate out as a precipitate phase. This invention achieves this by having an atomic ratio of Mg / Y+Dy+Ho+Er > 10:1, and an atomic ratio of Y, Dy, Ho, and Er of 1:1:1:1, thus enabling the formation of Mg after the rare earth atoms are dissolved. 24 (Y 0.25 Dy 0.25 Ho 0.25 Er 0.25 5. High-entropy particles, which, as reinforcements, possess high strength and high hardness, significantly improving the strength and hardness of composite materials; simultaneously, in-situ self-generated Mg 24 (Y 0.25 Dy 0.25 Ho 0.25 Er 0.25 5. High-entropy particles form a coherent interface with the Mg matrix, which can extend dislocations and coordinate the plastic deformation of the material. Results show that 15.61% Mg by volume... 24 (Y 0.25 Dy 0.25 Ho 0.25 Er 0.25 The high-entropy particle-reinforced composite material has a yield strength YS of 212 MPa, a tensile strength of 361 MPa, and a Vickers hardness of 91 Hv at room temperature (25°C), while also having an elongation of 10.6%. That is, this application can achieve a synergistic improvement in the room temperature strength and ductility of the alloy by generating high-entropy particle-reinforced Mg-based composite material in situ.

[0017] 2) The preparation method of the present invention involves in-situ generation of Mg 24 (Y 0.25 Dy 0.25 Ho 0.25 Er 0.25 )5 High-entropy particles effectively improve Mg / Mg 24 (Y 0.25 Dy 0.25 Ho 0.25 Er 0.255. Comprehensive mechanical properties at room temperature. This method is simple to operate, the process is controllable, the particles are uniformly dispersed and the interfacial bonding is good, making it suitable for large-scale production. Compared with traditional technologies, the in-situ generation of high-entropy particle reinforcements used in this invention has lower production costs and a simpler preparation process, and can maintain the material's strength and hardness while also possessing a high level of ductility. In addition, the volume fraction of high-entropy particle reinforcements can be reasonably controlled through composition design, which not only maintains the material's lightweight characteristics but also improves the room temperature mechanical properties of the composite material, showing strong industrial application prospects, especially in lightweight industries such as aerospace, automotive, and electronics, where it has broad application potential. Attached Figure Description

[0018] To more clearly illustrate the specific embodiments of the present invention, the accompanying drawings used in the description of the specific embodiments or the prior art will be briefly introduced below.

[0019] Figure 1 The phase diagram of existing magnesium alloy Mg-Y binary alloys is shown. Figure 2 The existing Mg-Dy binary alloy phase diagram is shown. Figure 3 The phase diagram of the existing magnesium alloy Mg-Ho binary alloy is shown. Figure 4 The existing Mg-Er binary alloy phase diagram is shown. Figure 5 This is a SEM image of the composite material provided in Example 2 of the present invention; Figure 6 The image shown is an XCT image of the composite material provided in Example 2 of this invention. Figure 7 This is a TEM image of the composite material provided in Example 2 of the present invention; Figure 8 AC-STEM image of the composite material provided in Example 2 of this invention; Figure 9 The mechanical properties of the extruded composite materials provided in Example 2 and Comparative Examples 1 and 2 of this invention are shown in the diagram. Detailed Implementation

[0020] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. The following embodiments are merely descriptive and not limiting, and should not be construed as limiting the scope of protection of the present invention.

[0021] When a quantity, concentration, or other value or parameter is described as a range, preferred range, or preferred upper and lower limits, it should be understood that it is equivalent to specifically disclosing any range by combining any pair of upper or preferred values ​​with any lower or preferred values, regardless of whether the range is specifically disclosed. Unless otherwise stated, the numerical range values ​​listed herein include the endpoints of the range and all integers and fractions within that range.

[0022] Unless otherwise stated, all percentages, parts, ratios, etc. in this document are by weight.

[0023] The materials, methods, and embodiments described herein are exemplary and should not be construed as limiting unless otherwise stated.

[0024] In the following examples, the raw materials of pure Mg, Mg-30wt.%Y, Mg-20wt.%Dy, Mg-30wt.%Ho, and Mg-30wt.%Er had an index of 99.98% and were purchased from Hunan Rare Earth Metal Materials Research Institute Co., Ltd. The test methods used in the following embodiments include: The strength, Vickers hardness, and ductility properties are demonstrated by testing the main properties of each test sample separately; the main properties tested in this application include strength, Vickers hardness, and ductility.

[0025] 1) Tensile test; The tensile test was performed using a CMT5105 instrument and the method for room temperature tensile testing of metallic materials, in accordance with the method specified in (GB / T 228.1-2021). 2) Vickers hardness test The Vickers hardness of the samples was tested using an HXS-1000AY instrument. Example 1 This embodiment provides a method for preparing in-situ high-entropy particle-reinforced magnesium-based composite materials, which includes the following steps: 1) Weigh out the following amounts of blocky pure Mg, Mg-30wt.%Y, Mg-20wt.%Dy, Mg-30wt.%Ho, and Mg-30wt.%Er according to the atomic ratio of Mg, Y, Dy, Ho, and Er of 130:1:1:1:1; 2) Add the weighed raw materials to a stainless steel crucible, introduce a protective gas (a mixture of CO2 and SF6 in a volume ratio of 99:1), place it in a melting furnace and heat it to 720°C until the base alloy is completely melted. After complete melting, mechanically stir the melt to ensure uniform composition and remove surface slag to obtain magnesium alloy base melt. Use crucible tongs to clamp the crucible and remove it from the melting furnace. Place it in cold water and slowly water-cool it around the crucible for 30 seconds to obtain an ingot. 3) The ingot obtained in step 2) is first homogenized and heat-treated at a temperature of 480℃ for 18 hours, and then extruded at an extrusion temperature of 480℃, an extrusion ratio of 15:1, and an extrusion rate of 1 mm / s to obtain an in-situ generated high-entropy particle-reinforced magnesium matrix composite material.

[0026] Example 2 This embodiment provides a method for preparing in-situ high-entropy particle-reinforced magnesium-based composite materials, which includes the following steps: 1) Weigh out the following amounts of blocky pure Mg, Mg-30wt.%Y, Mg-20wt.%Dy, Mg-30wt.%Ho, and Mg-30wt.%Er according to the atomic ratio of Mg, Y, Dy, Ho, and Er of 195:1.25:1.25:1.25:1.25; 2) Add the weighed raw materials to a stainless steel crucible, introduce a protective gas (a mixture of CO2 and SF6 in a volume ratio of 99:1), place it in a melting furnace and heat it to 720°C until the base alloy is completely melted. After complete melting, mechanically stir the melt to ensure uniform composition and remove surface slag to obtain magnesium alloy base melt. Use crucible tongs to clamp the crucible and remove it from the melting furnace. Place it in cold water and slowly water-cool it around the crucible for 30 seconds to obtain an ingot. 3) The ingot obtained in step 2) is first homogenized and heat-treated at a temperature of 520℃ for 16 hours, and then extruded at an extrusion temperature of 520℃, an extrusion ratio of 18:1, and an extrusion rate of 2 mm / s to obtain an in-situ generated high-entropy particle-reinforced magnesium matrix composite material.

[0027] Example 3 This embodiment provides a method for preparing in-situ high-entropy particle-reinforced magnesium-based composite materials, which includes the following steps: 1) Weigh out the following amounts of blocky pure Mg, Mg-30wt.%Y, Mg-20wt.%Dy, Mg-30wt.%Ho, and Mg-30wt.%Er according to the atomic ratio of Mg, Y, Dy, Ho, and Er of 100:1:1:1:1; 2) Add the weighed raw materials to a stainless steel crucible, introduce a protective gas (a mixture of CO2 and SF6 in a volume ratio of 99:1), place it in a melting furnace and heat it to 740°C until the base alloy is completely melted. After complete melting, mechanically stir the melt to ensure uniform composition and remove surface slag to obtain magnesium alloy base melt. Use crucible tongs to clamp the crucible and remove it from the melting furnace. Place it in cold water and slowly water-cool it around the crucible for 30 seconds to obtain an ingot. 3) The ingot obtained in step 2) is first homogenized and heat-treated at 520℃ for 12 hours, and then extruded at 420℃, extrusion ratio of 20:1 and extrusion rate of 2mm / s to obtain in-situ generated high-entropy particle-reinforced magnesium matrix composite material.

[0028] Comparative Example 1 This comparative example provides a method for preparing a magnesium-based composite material. The raw materials and proportions are basically the same as those in Example 2, except that the amounts of blocky pure Mg, Mg-30wt.%Y, Mg-20wt.%Dy, Mg-30wt.%Ho, and Mg-30wt.%Er are weighed according to the atomic ratio of Mg, Y, Dy, Ho, and Er of 195:0.5:0.5:0.5:3.5. The process steps and parameters are the same as those in Example 2.

[0029] The magnesium-based composite material in this comparative example will theoretically form Mg / Mg 24 (Y 0.1 Dy 0.1 Ho 0.1 Er 0.7 )5, while the number of Y, Dy, Ho and Er atoms differs greatly, so they cannot have a high entropy effect and therefore cannot form high entropy particle-reinforced magnesium matrix composites.

[0030] Comparative Example 2 This comparative example provides a method for preparing a magnesium-based composite material. The raw materials and proportions are basically the same as those in Example 2, except that the amounts of blocky pure Mg, Mg-30wt.%Y, Mg-20wt.%Dy, Mg-30wt.%Ho, and Mg-30wt.%Er are weighed according to the atomic ratio of Mg, Y, Dy, Ho, and Er of 195:0.5:0.5:1:3. The process steps and parameters are the same as those in Example 2.

[0031] The magnesium-based composite material in this comparative example may theoretically form Mg / Mg 24 (Y 0.1 Dy 0.1 Ho 0.2 Er 0.6 )5, while the number of atoms of Y, Dy, Ho and Er differs even more, so they cannot have a high entropy effect and therefore cannot form high entropy particle-reinforced magnesium matrix composites.

[0032] Experimental example: This experimental example uses Example 2 as an example to test the performance of the in-situ generated high-entropy particle-reinforced magnesium matrix composite material. Specifically: Experimental Examples 1-4: This experimental example analyzes the material technology of in-situ generated high-entropy particle-reinforced magnesium-based composites, and the results are as follows: Figure 1 As shown in the figure, Figure 1-4 The four figures represent binary alloy phase diagrams of Mg-Y, Mg-Dy, Mg-Ho, and Mg-Er, respectively. The figures show that when Mg:RE (Y:Dy:Ho:Er = 1:1:1:1) > 10:1, RE can undergo a hypoeutectic reaction with Mg simultaneously: 5RE + (24 + x)Mg → xMg + Mg 24 RE5, precipitates high-entropy phase Mg 24 (Y 0.25 Dy 0.25 Ho 0.25 Er 0.25 5. After homogenization treatment and hot extrusion process, a uniformly distributed Mg / Mg ratio is obtained. 24 (Y 0.25 Dy 0.25 Ho 0.25 Er 0.25 5. Composite materials.

[0033] Experimental Example 5: In this experimental example, the as-cast alloy in step 2) and the extruded alloy in step 3) of Example 2 were subjected to electron microscopy scanning, and their SEM images are shown below. Figure 5 As shown, where Figure 5 a shows the morphology of the network high-entropy phase in the as-cast state of the composite material; Figure 5 bc shows that after the composite material is extruded and deformed, fine high-entropy particles are formed, which are dispersed in the Mg matrix in the cross section and uniformly distributed along the extrusion direction in the longitudinal section; the high-entropy phase Mg can be seen from the figure. 24 (Y 0.25 Dy 0.25 Ho 0.25 Er 0.25 )5 exhibits a network distribution and is crushed into fine high-entropy particles after extrusion deformation. The high-entropy particles in the longitudinal section are distributed along the extrusion direction and are uniformly distributed in the cross section, indicating that the high-entropy particles precipitated in situ can be dispersed in the Mg matrix and maintain an excellent interfacial relationship with Mg.

[0034] Experimental Example 6: In this experimental example, the as-cast alloy in step 2) of Example 2 was subjected to XCT scanning, and the results are as follows: Figure 6 As shown, where Figure 6 a represents the original grayscale image of the composite material; Figure 6 b is a three-dimensional reconstruction of the composite material; as shown in the figure, the high-entropy phase in the as-cast state is uniformly distributed in three dimensions throughout the composite material; where Figure 6 c represents the volume fraction of the second phase in the composite material; Figure 6 d is a size statistics diagram of the composite material. As can be seen from the figure, the average size of the high-entropy phase of the composite material in this application is 15.53 μm, and its volume fraction accounts for 15.61% of the composite material, while the matrix Mg is 84.39%.

[0035] Experimental Example 7: This experimental example performs TEM analysis on the extruded alloy in step 3) of Example 2, and the results are as follows: Figure 7 As shown, (a) BF plot; (b) SAED diffraction spots; (c) EDS-Pointing plot; (d) EDS-Mapping plot; Figure 7 ab shows the morphology of the high-entropy phase under transmission light, and analysis of the diffraction spots reveals that its crystal structure is Mg. 24 RE5; where Figure 7 The surface scan of cd shows that it simultaneously contains Mg, Y, Dy, Ho, and Er, and the atomic ratio of Y:Dy:Ho:Er is close to 1:1:1:1, indicating that it forms high-entropy Mg particles. 24 (Y 0.25 Dy 0.25 Ho 0.25 Er 0.25 5; Experimental Example 8: This experimental example performs AC-STEM analysis on the extruded alloy from step 2) of Example 2, and the AC-STEM image is shown below. Figure 8 As shown in Figures 8a-b, (a) is the BF-S diagram; (b) is the FFT diagram; and (cd) are the HAADF-S diagrams and GPA diagrams of the two interfaces. Figures 8a-b show the morphology of the high-entropy particles under spherical aberration transmission, and the interface is analyzed by diffraction spots, indicating that the Mg content of the particles is high. 24 (Y 0.25 Dy 0.25 Ho 0.25 Er 0.25 )5 and Mg form a coherent interface; Figure 8 The coherent atomic arrangement of the two interfaces was analyzed by CD, and the mismatch degree was 0. The low interfacial stress was analyzed by GPA, indicating excellent interfacial bonding. This shows that there is a certain orientation relationship between the high-entropy particles and the matrix, with good coherence and low internal stress.

[0036] Experimental Example 9: This experimental example tested the mechanical properties of the extruded alloys in Example 2, Comparative Examples 1 and 2, and the results are as follows: Figure 9 As shown, the left side is the tensile curve; the right side is the Vickers hardness histogram; from... Figure 9 Knowing Mg / Mg 24 (Y 0.25 Dy 0.25 Ho 0.25 Er 0.25 5. Extruded tensile strength: 361.8 ± 7.0 MPa; yield strength: 212.4 ± 4.8 MPa; ductility: 10.6% ± 1.0%; hardness: 107.4 ± 3.0 Hv; Mg / Mg ratio: 24 (Y 0.1 Dy 0.1 Ho 0.1 Er 0.7 5. Extrusion tensile strength: 338.9 ± 4.9 MPa, yield strength: 152.7 ± 3.1 MPa, ductility: 6.4% ± 2.1%, hardness: 97.1 ± 1.5 Hv; Mg / Mg 24 (Y 0.1 Dy 0.1 Ho 0.2 Er 0.6 The tensile strength under extrusion was 354.5 ± 2.8 MPa, the yield strength was 170.0 ± 2.1 MPa, the ductility was 8.1% ± 1.5%, and the hardness was 102.1 ± 2.7 Hv. The results show that the magnesium matrix composite reinforced with high-entropy particles has a more significant effect on the synergistic improvement of strength and ductility.

[0037] Experimental Example 10: In this experimental example, the configuration entropy of the extruded alloys in Example 2, Comparative Examples 1 and 2 was calculated at different points using the following formula: The results are shown in the table below: The calculation results in the table show that the reinforcing agent Mg in Experimental Example 1... 24 (Y 0.25 Dy 0.25 Ho 0.25 Er 0.25 )5 of ΔS conf The value is 1.40R; the reinforcing Mg in Comparative Example 1 24 (Y 0.1 Dy 0.1 Ho 0.1 Er 0.7 )5 of ΔS conf The value is 0.94R; the reinforcing Mg in Comparative Example 224 (Y 0.1 Dy 0.1 Ho 0.2 Er 0.6 )5 of ΔS conf The value is 1.08R. Currently, there is no definitive numerical value for the configurational entropy of high-entropy alloys; it is generally believed that when the number of principal elements is ≥4, ΔS... conf When R is ≥1.4, it is easier for Mg to form a single-phase solid solution, therefore Mg 24 (Y 0.25 Dy 0.25 Ho 0.25 Er 0.25 )5 are high-entropy particles, while Mg 24 (Y 0.1 Dy 0.1 Ho 0.1 Er 0.7 5. Mg 24 (Y 0.1 Dy 0.1 Ho 0.2 Er 0.6 )5 is a non-high-entropy particle.

[0038] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be covered within the scope of the claims and specification of the present invention.

Claims

1. An in-situ generated high-entropy particle-reinforced magnesium-based composite material, characterized in that, The composite material includes Mg, Y, Dy, Ho and Er elements, the atomic ratio of Mg / Y+Dy+Ho+Er is >10:1, and the atomic ratio of Y, Dy, Ho and Er is 1:1:1:

1.

2. A method for preparing an in-situ generated high-entropy particle-reinforced magnesium matrix composite material according to claim 1, characterized in that, Includes the following steps: 1) According to the formula requirements, the composite material raw materials are mixed and melted, then poured into a mold, and after cooling, an alloy ingot is obtained; 2) The alloy ingot obtained in step 1) is homogenized and extruded to obtain an in-situ high-entropy particle-reinforced magnesium matrix composite material.

3. The method for preparing in-situ high-entropy particle-reinforced magnesium-based composite materials according to claim 2, characterized in that, The mixing and melting described in step 1) specifically refers to mixing and melting under protective gas conditions.

4. The method for preparing in-situ high-entropy particle-reinforced magnesium-based composite materials according to claim 3, characterized in that, The mixing and melting step described in step 1) is specifically as follows: Under protective gas conditions, the prescribed amounts of Mg, Y, Dy, Ho and Er elements are heated and melted. After the base alloy is completely melted at 720-740℃, it is stirred evenly to obtain a magnesium alloy base melt.

5. The method for preparing in-situ high-entropy particle-reinforced magnesium-based composite materials according to claim 4, characterized in that, The protective gas is a mixture of CO2 and SF6 in a volume ratio of 99:

1.

6. The method for preparing in-situ high-entropy particle-reinforced magnesium-based composite materials according to claim 5, characterized in that, The cooling described in step 1) is water cooling, which specifically involves placing the ingot in cold water and slowly cooling it around the crucible for 30-60 seconds.

7. The method for preparing in-situ high-entropy particle-reinforced magnesium-based composite materials according to claim 1, characterized in that, The homogenization heat treatment in step 2) is performed at a temperature of 480-520℃ for 12-18 hours.

8. The method for preparing in-situ high-entropy particle-reinforced magnesium-based composite materials according to claim 7, characterized in that, The extrusion molding conditions described in step 2) are: extrusion temperature 420-480℃, extrusion ratio (15-20):1, and extrusion speed 0.5-2.0mm / s.